Phospholipid Phosphatase 4 as a Driver of Malignant Glioma and Pancreatic Adenocarcinoma - Tian, Wenxiu; Wang, Ping; Wang, Zhimei; Qi, Huimin; Dong, Junhong; Wang, Hongmei (Frontiers in Oncology, 2021)
Glioma and pancreatic cancer are tumors with a high degree of malignancy, morbidity, and mortality. The present study explored possible molecular mechanisms and potential diagnostic and prognostic biomarkers of glioma and PAAD. The prognostic value of the genes was evaluated using survival analysis of TCGA data. Following this, the protein expression pattern of the candidate genes was detected in clinical tissue samples. We further performed a retrospective clinical study of the expression of candidate protein-PLPP4 and the survival time of patients. Moreover, the combination of multiple proteins for the prognosis prediction of glioma and PAAD was evaluated. In vitro experiment was conducted to elaborate the potential roles of these biomarkers in clonability and invasion of glioma and PAAD cells.